Bed Rest in Deep Vein Thrombosis and the Incidence of Scintigraphic Pulmonary Embolism - Schellong, Sebastian M.; Schwarz, Thomas; Kropp, Joachim; Prescher, Yvette; Beuthien-Baumann, Bettina; Daniel, Werner G. (Thrombosis and Haemostasis, 1999)
In several countries of central Europe, patients with acute proximal deep vein thrombosis (DVT) are treated not only by anticoagulation and compression therapy but additionally by strict bed rest for 6-8 days. Until now the theoretical assumption that bed rest substantially reduces the incidence of pulmonary embolism has not been subjected to empirical verification. Patients with acute proximal DVT proven by ultrasonography were randomly assigned to strict bed rest for 8 days (treatment group) or to stay mobilised (control group). In both groups, basic treatment consisted in anticoagulation by subcutaneous low molecular weight heparin/vitamin-K-antagonist and compression therapy. The incidence of pulmonary embolism was assessed by serial ventilation/perfusion SPECT on day 1 and days 8-10. Of the 309 patients with proximal DVT considered for inclusion, 180 were excluded according to the study protocol, and 3 did not give informed consent. One hundred and twenty-six patients were randomly assigned to observe bed rest (n = 62) or to keep mobilised (n = 64). Four patients refused follow-up lung scan.A new lung perfusion defect was detected in 10/59 patients in the treatment group compared to 14/63 patients in the control group (one-sided p-value = 0.25; power 0.8). Bed rest as an additional measure in the treatment of DVT is not able to substantially reduce the incidence of scintigraphically detectable pulmonary embolism. The discomfort and costs associated with the prescription of bed rest in DVT are obviously inappropriate.
Keywords: Deep vein thrombosis; pulmonary embolism; lung scintigraphy; bed rest